Association of Serum Homocysteine and Serum Lipid with Eclampsia (Journal of Armed Forces Medical College, Bangladesh, 2009)
Eclampsia is one of the most common pregnancy complications causing high mortality and morbidity for both mother and foetus especially in developing countries. Many studies suggest that elevated homocysteine level is an important risk factor for eclampsia. The aim of this study was to explore the association between serum homocysteine with eclampsia and to establish serum homocysteine measurement as a reliable test for early detection of eclampsia. In a case control study serum homocysteine and lipid profile were measured in 52 controls (healthy uncomplicated pregnant women) and 50 eclamptic pregnant women. Serum homocysteine in eclampsia cases (10.44±4.08 μmol/L) found to be significantly increased (p < 0.001) compared to controls (7.97±3.46 μmol/L). Serum HDL-cholesterol concentration found to be significantly decreased (p < 0.001) in the cases (35.98±6.35 mg/dl) compared to controls (42.69±6.09 mg/dl). A significant negative correlation (r-.801, p < 0.01) was found between serum homocysteine and HDL-cholesterol concentration among cases. It can be concluded that elevated serum homocysteine and HDL-cholesterol deficiency were associated with eclampsia. But elevated homocysteine itself might be a factor associated with eclampsia irrespective of lipid profile status. Key Words: Homocysteine, Eclampsia.   doi: 10.3329/jafmc.v5i1.2842 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.7-10